IgG3+ B cells are associated with the development of multiple sclerosis. Issue 5 (29th April 2020) - Marsh‐Wakefield, Felix; Ashhurst, Thomas; Trend, Stephanie; McGuire, Helen M; Juillard, Pierre; Zinger, Anna; Jones, Anderson P; Kermode, Allan G; Hawke, Simon; Grau, Georges E; Hart, Prue H; Byrne, Scott N
Abstract: Objectives: Disease‐modifying therapies (DMTs) targeting B cells are amongst the most effective for preventing multiple sclerosis (MS) progression. IgG3 antibodies and their uncharacterised B‐cell clones are predicted to play a pathogenic role in MS. Identifying subsets of IgG3 + B cells involved in MS progression could improve diagnosis, could inform timely disease intervention and may lead to new DMTs that target B cells more specifically. Methods: We designed a 31‐parameter B‐cell‐focused mass cytometry panel to interrogate the role of peripheral blood IgG3 + B cells in MS progression of two different patient cohorts: one to investigate the B‐cell subsets involved in conversion from clinically isolated syndrome (CIS) to MS; and another to compare MS patients with inactive or active stages of disease. Each independent cohort included a group of non‐MS controls. Results: Nine distinct CD20 + IgD − IgG3 + B‐cell subsets were identified. Significant changes in the proportion of CD21 + CD24 + CD27 − CD38 − and CD27 + CD38 hi CD71 hi memory B‐cell subsets correlated with changes in serum IgG3 levels and time to conversion from CIS to MS. The same CD38 − double‐negative B‐cell subset was significantly elevated in MS patients with active forms of the disease. A third CD21 + CD24 + CD27 + CD38 − subset was elevated in patients with active MS, whilst narrowband UVB significantly reduced the proportion of this switched‐memory B‐cell subset. Conclusion: We have identified previously uncharacterised subsets of IgG3 + B cells and shown them to correlate with autoimmune attacks on the central nervous system (CNS). These results highlight the potential for therapies that specifically target IgG3 + B cells to impact MS progression. Abstract : Mass cytometry has allowed us to identify nine unique IgG3 + B‐cell subsets. Using two independent cohorts of multiple sclerosis (MS) patients, we show that a number of these IgG3 + subsets are not only associated with MS progression but also affected by disease‐modifying therapies. These studies highlight the potential for therapies that specifically target IgG3 + B cells to impact MS progression.